The use of the concept of “totalitarianism” in antiperonista political literature. The case of Reynaldo Pastor’s Frente al totalitarismo peronista (Quinto Sol, 2017)
This article analyses the book written by Reynaldo Pastor and entitled Frente al totalitarismo peronista as a late result of antiperonista literature. The mentioned text exposes the mixing of a liberal-conservative antifascist tradition with a renewed anti-totalitarian Cold War preaching. In this work, we indicate the importance of the role that political taxonomy played as a way to make believable the idea of consistency between peronismo and totalitarianism. As a novelty, it can be noted the use of a two-columns design in the strategy of the author of the reported book to confirm the identity between peronismo and communism.
Keywords: antiperonismo; anti-totalitarianism; antifascism; anticommunism; Cold War